Constitutional design and political agency problems: the case of Colombia (2014)
This article presents and explores, from a law and economics’ perspective, the Colombian Constitutional structures that create potential for corruption by undermining the checks and balances, the accountability system over politicians and in particular, by altering the computation of the agent once is facing the decision to act according to principal interest or behave in a corrupt way. A case study from a Colombian high court is presented in order to illustrate the interaction between the identified constitutional provisions to generate a scope for corruption. Finally, possible constitutional amendments are suggested in order to overcome these system failures.